2022
DOI: 10.3390/cancers14184484
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity in Quadruple Negative Breast Cancer: Aggressive Biology and Potential Therapeutic Targeting and Prevention

Abstract: Black/African-American (AA) women, relative to their White/European-American (EA) counterparts, experience disproportionately high breast cancer mortality. Central to this survival disparity, Black/AA women have an unequal burden of aggressive breast cancer subtypes, such as triple-negative breast cancer (ER/PR-, HER2-wild type; TNBC). While TNBC has been well characterized, recent studies have identified a highly aggressive androgen receptor (AR)-negative subtype of TNBC, quadruple-negative breast cancer (ER/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 118 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…MiRNA profiling of the TNBC tumor cells (and of several other types of tumors) can vary according to the populational group studied [20,26,[39][40][41][42][43][44]. Most of the data are, however, in the comparison of NHW to AA TNBC patients [26,40,[44][45][46][47]. In our previous study, we reported that ancestrally characterized AA patients, when compared to NHW, exhibited distinct patterns of copy number alterations (CNAs) and miRNA expression profiles in both their TNBC and non-TNBC tumor tissues [44].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA profiling of the TNBC tumor cells (and of several other types of tumors) can vary according to the populational group studied [20,26,[39][40][41][42][43][44]. Most of the data are, however, in the comparison of NHW to AA TNBC patients [26,40,[44][45][46][47]. In our previous study, we reported that ancestrally characterized AA patients, when compared to NHW, exhibited distinct patterns of copy number alterations (CNAs) and miRNA expression profiles in both their TNBC and non-TNBC tumor tissues [44].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies 25 have reported that African American females have higher rates in general of QNBC, a TNBC subtype characterized by the lack of AR expression. Our data suggest that the higher incidence of QNBC may be specific to younger African American patients, demonstrated by the significant downregulation of AR in TNBC tumors of this population compared with older African American patients.…”
Section: Discussionmentioning
confidence: 98%
“…African American (AA) women have significantly higher mortality rates from breast cancer (BC) than White (W) women with the same disease and patient variables despite having a lower incidence of disease [ 1 , 2 , 3 , 4 , 5 , 6 ]. Genetic [ 7 ] and epigenetic [ 8 ] differences in cancer cells [ 9 ] and genetic, immune, and inflammatory differences and vitamin D deficiency in the tumor microenvironment [ 8 , 10 , 11 ] contribute to more aggressive cancer characteristics and, in combination with extensive and well-documented socioeconomic factors [ 12 , 13 ], collectively generate a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%